2019
DOI: 10.1093/cid/ciz1146
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance Development Following Colistin-Meropenem Combination Therapy Versus Colistin Monotherapy in Patients With Infections Caused by Carbapenem-Resistant Organisms

Abstract: Background We evaluated whether carbapenem-colistin combination therapy reduces the emergence of colistin resistance, compared to colistin monotherapy, when given to patients with infections due to carbapenem-resistant Gram-negative organisms. Methods This is a pre-planned analysis of a secondary outcome from a randomized, controlled trial comparing colistin monotherapy with colistin-meropenem combination for the treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The synergistic activity often manifests through prevention of bacterial regrowth, which occurs commonly in vitro against single agents, particularly colistin. The impact of the colistin–carbapenem combinations on the delay in the emergence of resistance remains to be elucidated given conflicting reports of both clinical successes and failures [ 61 , 66 ]. Decreased susceptibility to colistin may inhibit in vitro synergy and prompt clinicians to explore alternative therapies, including three-drug combinations [ 62 ].…”
Section: Mechanistic Insights Into Antibiotic Combinationsmentioning
confidence: 99%
“…The synergistic activity often manifests through prevention of bacterial regrowth, which occurs commonly in vitro against single agents, particularly colistin. The impact of the colistin–carbapenem combinations on the delay in the emergence of resistance remains to be elucidated given conflicting reports of both clinical successes and failures [ 61 , 66 ]. Decreased susceptibility to colistin may inhibit in vitro synergy and prompt clinicians to explore alternative therapies, including three-drug combinations [ 62 ].…”
Section: Mechanistic Insights Into Antibiotic Combinationsmentioning
confidence: 99%
“…This was examined as a secondary outcome in the AIDA trial. We found no difference in the emergence of colistin resistance between individuals randomized to colistin monotherapy (9.4%) versus colistin-meropenem combination therapy (11.1%) (p 0.67) [2].…”
Section: To the Editormentioning
confidence: 63%
“…A recent retrospective cohort study found that combination therapies, mostly polymyxin B plus amikacin, had signi cantly lower 30-day mortality rates than monotherapies (37.5% vs. 64.75%, p = 0.01) in 82 patients with CRKP-BSIs (28). However, reports still emerge of inadequate dosages, treatment failures, adverse effects, and heterogeneous resistance during polymyxin B treatment (29).…”
Section: Discussionmentioning
confidence: 99%